Impact of Local Economic Development Programmes on Livelihood: Evidence from Mpumalanga, South Africa - Kanayo, Ogujiuba; Ndlovu, Portia; Agholor, Isaac (International Journal of Economics and Financial Issues, 2021)
Extraordinary levels of unemployment, poverty and inequality perseveres in South Africa, which in itself is a risk for economic development. Initiatives such as Local Economic Development (LED), globally acknowledged, have been adopted to solve the crisis. LED in its simplest practice is about local people uniting to achieve a better quality of life. Nevertheless, effects of LED are still contentious in developing economies and especially South Africa because of the increased level of poverty amongst supposed beneficiaries of LED. This article evaluates the impact of a LED initiative (EPWP) on reducing the triple challenges facing South Africa. A mixed method approach and a paired-sample t-test was performed to determine the effect of LED. Between time 1[M=17.91, SD=2.68] to time 2[M=20.06, SD=3.43, t(44)=5.1429, p<.0005], there was a statistically significant increase in EPWP ratings by participants. The statistic of eta squared (.375) showed a large effect size. EPWP has generated income and increased skills showing a change in some areas, because of the programme. Qualitative findings indicate that LED evidently has a role to play concerning poverty and unemployment relief, but the initiative is not enough. This article recommends the establishment of projects, which will provide sufficient livelihood for local beneficiaries, which will facilitate local participation. Keywords: EPWP, LED, Livelihood, Poverty JEL Classifications: O20, O21, O38 DOI: https://doi.org/10.32479/ijefi.11589